Research on Topology and Parameter Design of a Novel Flexible On-Load Voltage Regulator. Issue 1 (1st December 2022) - Han, Li-bo; Yin, Jing-yuan; Sun, Long-fei; Wu, Li-xin; Wei, Tong-zhen
Abstract: Traditional on-load tap charger (OLTC) transformer use mechanical switch or anti-parallel thyristor as on-load tap changers. By changing the position of the tap chargers, the transformation ratio is changed, so as to achieve discrete step voltage regulation function. In this paper a novel Flexible On-Load Voltage Regulator (Flexible OLVR) is proposed, which is integrated design of Power Electronic Converter (PEC) and OLTC transformer. The converter is set at the primary side of the transformer, and it could control the output voltage accurately to relize the stepless voltage regulation when there is grid voltage fluctuation. The topology and operating principle of 10kV/0.4kV Flexible OLVR are given in this paper. Secondly, the main parameter design criteria is discussed through a group of design examples. Finally, the feasibility of the scheme is verified by the simulation waveform.